Pelatihan Pengembangan Industri Rumahan di Bidang Food and Beverage untuk Mendukung Pariwisata di Kampung Sawah, Kota Tangerang - Veronica, Veronica; Sarudin, Rendy; Tirtadijaja, Andari; Nawangwulan, Wening (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This Community Service activity aims to empower women in Kampung Sawah Dalam, Kota Tangerang, through training in the field of food and beverage (F&B). This program supports the development of home-based businesses while fostering the growth of the local community economy. The materials covered include production techniques, packaging, product labeling, marketing strategies, and basic English training. The event was held on Friday, October 18, 2024, and was attended by 46 enthusiastic participants. The activity began with a preparation phase, including discussions with the neighborhood head to identify the specific needs of the participants. In the training sessions, participants received materials on tourism introduction, demonstrations on making appetizers and beverages, as well as training in marketing and English. During practice sessions, participants made canapés and fruit punch, which provided them with valuable hands-on experience. The evaluation showed positive results. Participants rated the training as highly educational, relevant to their needs, easy to understand, and interactive. The materials were considered useful for enhancing participants' skills in managing small businesses. This program successfully increased their understanding of business management, financial services, and motivated them to manage their businesses more effectively. Recommendations for future improvements include extending the training duration, expanding the number of participants, and adding more practical sessions to maximize the program's impact. Keywords: Training, Home-based Industry, Food and Beverage, Tourism, MSMEs